Determinantes da assistência obstétrica e neonatal para sífilis congênita no seguimento clínico em ambulatório de referência - Lorena Batista Pascoal (2023)
Introduction – Despite being an old and treatable disease, syphilis remains a public health problem in Brazil and around the world. Among its complications is congenital syphilis (CS), which results from the transmission of the spirochete Treponema pallidum from the infected pregnant woman to the conceptus. The only form of prevention of CS is the diagnosis and timely treatment of the infected pregnant woman. Thus, the identification of variables that are associated with vertical transmission of syphilis is an important measure for the creation of policies focusing on the risk population and the consequent correction of failures in health care procedures. Objective – To identify and analyze the factors associated with obstetric and newborn (NB) care that can serve as predictors of CS. Method – A retrospective cohort study was carried out at the Reference and Training Center in Infectious and Parasitic Diseases (RTC) Orestes Diniz, from 2017 to 2022. Non-probabilistic sampling was used, and children treated due to vertical exposure to syphilis were included. The definition of confirmed CS was based on the presence of a positive treponemal test after 18 months of life, and discarded CS was defined as having a negative treponemal test. The statistical analysis of the data was conducted using the Statistical Package for Social Sciences (SPSS) 21.0 software (IBM, Armonk, NY). In the descriptive analysis, continuous variables were expressed as mean and standard deviation or median and interquartile range, depending on their distribution. Categorical variables were presented as frequency and percentage. The comparative analysis of the variables between the groups of children with confirmed and discarded CS diagnoses included the Mann-Whitney test for continuous variables and the exact Fisher test for categorical variables. Statistical significance was considered at p<0.05, and the measure of the magnitude of the association was evaluated by the odds ratio (OR) and confidence interval (CI) of 95%. The study is a branch of the Research Project approved by the Ethics and Research Committee (COEP) of UFMG entitled “Diagnosis of congenital infections and correlation with fetal involvement and clinical evolution of children infected by vertical transmission”. Results – Of 867 eligible patients, 377 children were included in the comparative analysis, of which ten (2.7%) had a confirmed diagnosis of CS and 367 (97.3%) had it discarded. The prevalence of CS in our study was 1.15% (10/377). The diagnosis of syphilis was confirmed in 221 women (58.6%), and the treatment for syphilis was considered adequate in 58 (17.7%). Clinical manifestations were documented in 77 children (20.4%), namely splenomegaly (n=3), hepatomegaly (n=6), exanthema (n=2), jaundice (n=61), petechiae (n=2) and delay in neuro-psychomotor development (n=3) and treatment for syphilis was carried out in 81.2% of patients (n=306). Three variables were independently associated with CS: absence of maternal treatment with benzathine penicillin (OR=4,29; CI 95% 1,13-18,96), clinical manifestations present in the neonatal period or at the first clinic appointment (OR=4,97; CI 95% 1,30-18,96), and titration of VDRL (Venereal Disease Research Laboratory) of the NB collected at the maternity > 1:2 (OR=11,28; CI 95% 1,42-94,44). Conclusion – Despite being a preventable disease, CS remains a public health problem. The high percentage of inadequately treated mothers reflects the difficulties in managing infected pregnant women, which in turn significantly increases the risk of CS occurrence. Furthermore, although clinical manifestations in the neonatal period have been identified as factors associated with CS, the non-specificity of these findings contributes to the complexity of the proper management of NBs exposed vertically to syphilis. The altered VDRL result in the newborn, identified as an independent variable associated with the final diagnosis of CS, highlights the importance of valuing this test in the decision to treat the RN at the maternity hospital. Keywords: congenital syphilis; maternal syphilis; prenatal care; risk factors; vertical infectious disease transmission.